The impact of drought in 2015 on the health forest condition determined using Landsat-8 OLI images - Nasiłowska, Sylwia; Kacprzak, Mariusz; Kotlarz, Jan; Kubiak, Katarzyna; Rotchimmel, Karol; Rynkiewicz, Alicja (Leśne Prace Badawcze, 2019)
The main aim of this research was to determine the impact of drought (in 2015) on forests stand condition using remote sensing and statistical techniques. The study was based on the analysis of vegetation indices calculated from a series of Landsat-8 OLI satellite images covering the 2014 and 2015 growing seasons. Various tree biophysical and physical parameters as well as forest habitat characteristics were tested in order to find the most significant factors affecting drought resistance. Three approaches were used: (i) index differences, (ii) PCA analysis, and (iii) ANOVA statistical analysis. All three approaches used in this study indicate that forest biodiversity is the most important factor determining habitat response to stress conditions. Coniferous and mixed tree habitats were less sensitive than deciduous ones. Statistical analysis revealed the relationship between stress and soil types, as those more permeable were less dependent on rainwater. The highest stress was found for precipitation-dependent gley soils. Undergrowth density and height were also indicated as important factors inducing habitat response to a changing weather situation. All the results confirmed the usefulness of mid-infrared based indices for water shortage monitoring in forests. They confirmed that habitat biodiversity has a positive effect on its resistance to stressful conditions. Also forest type (conifer/deciduous) determines it’s sensitivity. Precipitation and groundwater shortages have different effects on the forest condition depending on soil type.